SWALLOWING STRATEGY AND ORAL MOTOR EXERCISE FOR PREVENTION OF ASPIRATION IN STROKE PATIENTS - Muhammad Ardi (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
Stroke is a disorder of cerebral blood flow characterized by loss of focal and global nervous system function manifested by paralysis of one side of the body and neurological symptoms. Stroke patients also have difficulty swallowing and are at risk of experiencing aspiration. The case study method uses descriptive design and preventive aspiration exercises. The results of the case study of the 50-year-old suddenly experience weakness on the left side of the body so that they cannot walk with the mouth stuck and difficulty swallowing. Nursing intervention to prevent aspiration by adjusting the position of semi fowler when eating and maintaining the position for 30-45 minutes after eating, adjusting the head position when eating/drinking, encouraging the opportunity to swallow and cut small food, teach oral motor exercise. After five days of treatment, the patient is still coughing, the family has not yet been treated, so the patient does not choke, but has not been able to follow the whole series of oral exercises that have just been taught once. Based on this, nurses should have a swallowing screen in stroke patients, strategies for stroke patients who experience swallowing disorders to prevent aspiration.